Polarisasi Politik di Lingkungan Pondok Pesantren dalam Pemilihan Umum 2024 - Zahro, Fatimatuz; Saputri, Fenolia Intan (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
In the 2024 elections, the role of Islamic boarding schools will be very central, how could it not be that even before the campaign began, various elements of political parties as election participants flocked to various Islamic boarding schools in Indonesia in the hope of getting full support from scholars, Kyai and even santri and making Islamic boarding schools one of the bases for political battles ahead of elections which could potentially lead to polarization. The purpose of this research is to analyze political polarization in pesantren during the general election period and the impact it has. This research is normative juridical type with statutory, conceptual and historical approaches. The results showed that political polarization in the pesantren environment during the general election campaign period showed that pesantren had an important role in Indonesia's political process. However, this polarization also brings negative impacts in the form of internal fragmentation, political exploitation, and a decrease in the quality of democracy. Therefore, it is important to maintain the integrity and main function of pesantren as educational and moral institutions, and prioritize the principle of tolerance to maintain the integrity of political dynamics.